Liquid phase synthesis of aromatic poly(azomethine)s, their physicochemical properties, and measurement of ex situ electrical conductivity of pelletized powdered samples. Issue 1 (1st January 2017) - Hafeez, Abdul; Akhter, Zareen; Gallagher, John F.; Siddiqui, Humaira M.
Abstract: Aromatic bis -aldehydes have been used as building blocks in the synthesis of polyazomethines (a class of conjugated Schiff bases) and their physicochemical properties have been studied. Six dialdehydes have been synthesized, 3a-3f, via etherification reaction between aromatic diols (2a-2f ) and 4-fluorobenzaldehyde (1 ) (see Scheme1 ), and then polymerized with 1, 4-phenylenediamine (4a ) and 4, 4′-oxydianiline (4b ) (see Scheme2 ). The chemical structures of the bis -aldehydes were elucidated by FTIR, 1 H NMR and 13 C NMR spectroscopic studies, elemental analysis and single crystal whereas the polymers were studied by FTIR and NMR spectroscopy. Their physicochemical properties were examined by their inherent viscosity, organosolubility, differential scanning calorimetry, X-ray powder diffraction, thermogravimetric analysis, solvatochromism, and photoluminescence. We report the electrical conductivity of each polymer measured by the four probe method. The results indicate that the electrical conductivity of polymers lies in range 0.019–0.051 mScm −1 which is reasonably higher than any reported value.